Type 2 Diabetes Mellitus in Patients with Periodontitis at a Tertiary Care Hospital: A Cross-Sectional Study - Shrestha, Sweta; Agrawal, Shweta; Thakur, Amresh; Bhattarai, Rosina (Medical Journal of Armed Police Force Nepal, 2026)
Introduction: Periodontitis is a chronic inflammatory disease affecting the tissues surrounding the teeth. Bacteria or bacterial products may enter the general circulation through the ulcerated periodontal pocket, and cytokines produced locally will also have systemic effects, altering the body’s internal environment and causing insulin resistance. The aim of this study was to determine glycemic parameters among patients diagnosed with chronic periodontitis. Methods: This descriptive, cross-sectional study was conducted among 350 patients diagnosed with chronic periodontitis at a tertiary-level hospital from February 2025 to August 2025. Ethical approval was obtained from the Institutional Review Committee (Ref 030/2024). The patients were recruited by convenience sampling, written informed consent was obtained and they were sent for glycemic parameters. Data were entered in Statistical Package for the Social Sciences version 21 and Microsoft Excel 2019. Chi-square test was utilized to compare categorical data. Results: Among 350 participants with periodontitis, the majority, 219 (62.60%) had normal glycemic levels. However, a substantial proportion showed dysglycemia in which 87 (24.90%) were classified as having pre-diabetes and 44 (12.60%) had diabetes mellitus. The chi-square test suggested that, with progression of periodontitis, poor glycemic control was observed, and periodontitis staging showed significant associations with glycemic status (p < 0.001). Conclusions: Glycemic parameters were higher in patients with periodontitis. The study showed a significant correlation between the severity of periodontitis and poor glycemic control.